Location matters! Geospatial dynamics of MP responses to Covid-19 protests in multilevel systems - Lennart Schürmann; Jan Schwalbach; Noam Himmelrath (European Journal of Political Research, 2024)
In liberal democracies, protest can serve as a trigger for necessary policy reforms, but it can also be used by a loud minority to advance political goals against the will of the majority. Focusing on such vocal protests in the context of the Covid-19 pandemic, we investigate the following question: How does the location of protest events affect the likelihood of political engagement with the protests in a multilevel system? Combining social movement literature with studies of issue attention and rhetorical responsiveness, we analyze how German members of parliaments' (MPs) responses vary using their tweets from the onset of the pandemic to the German federal election in September 2021. Using quantitative text analysis, we measure rhetorical responsiveness to Covid-19 protests and apply multilevel regression analyses and difference-in-differences. We find that more protests lead to more attention; however, MPs respond most strongly to protests within the state they represent. Furthermore, politicians' level within the German multilevel system affects their attention to these protests, with MPs elected at lower levels of an electoral system responding more to local protest events than MPs elected at higher levels. The results highlight the importance of the location of protests in attracting political attention.
Keywords: 320; Covid-19 protest; rhetorical responsiveness; social media; multilevel systems; German politics